New Genotypes of Enterocytozoon bieneusi Isolated from Sika Deer and Red Deer in China - Huang, Jianying; Zhang, Zhenjie; Yang, Yong; Wang, Rongjun; Zhao, Jinfeng; Jian, Fuchun; Ning, Changshen; Zhang, Longxian (Frontiers in Microbiology, 2017)
To examine the occurrence and genotype distribution of Enterocytozoon bieneusi in cervids, 615 fecal samples were collected from red deer (Cervus elaphus) and sika deer (Cervus nippon) on 10 different farms in Henan and Jilin Province. Enterocytozoon bieneusi was identified and genotyped with a nested PCR analysis of the internal transcribed spacer (ITS) region of the rRNA genes, showing an average infection rate of 35.9% (221/615). In this study, 25 ITS genotypes were identified including seven known genotypes (BEB6, EbpC, EbpA, D, HLJDI, HLJD-IV, and COS-I) and 18 novel genotypes (designated JLD-I to JLD-XIV, HND-I to HND-IV). Among these, BEB6 (131/221, 59.3%) was the predominant genotype (P < 0.01), followed by HLJDI (18/221, 8.1%) and JLD-VIII (16/221, 7.2%). BEB6 has recently been detected in humans and nonhuman primates in China. The phylogenetic analysis showed that BEB6, HLJDI, HLJD-IV, COS-I, and 10 novel genotypes (JLD-VII to JLD-XIV, HND-III to HND-IV) clustered in group 2. Genotype D, EbpC, and EbpA, known to cause human microsporidiosis worldwide, clustered in group 1, the members of which have zoonotic potential, together with eight novel genotypes (JLD-I to JLD-VI, HND-I to HND-II). Therefore, deer may play a role in the transmission of E. bieneusi to humans. Key words: Enterocytozoon bieneusi, genotyping, internal transcribed spacer, deer.